Dietary supplementation with Dendrobium officinale leaves improves growth, antioxidant status, immune function, and gut health in broilers - Zhao, Wanqiu; Chen, Yue; Tian, Yong; Wang, Yunzhu; Du, Jianke; Ye, Xuan; Lu, Lizhi; Sun, Chongbo (Frontiers in Microbiology, 2023)
Background The Dendrobium officinale leaves (DOL) is an underutilized by-product with a large biomass, which have been shown to exhibit immunomodulatory and antioxidant functions. The purpose of this research was to investigate the effects of DOL on broiler growth performance, antioxidant status, immune function, and gut health. Methods One hundred and ninety-two 1-day-old chicks were selected and divided into 4 groups at random, 6 replicates for each group and 8 in each. Chicks were given a basal diet supplemented with different amounts of DOL: 0% (control group, NC), 1% (LD), 5% (MD), or 10% (HD). During the feeding trial (70 days), broiler body weight, feed intake, and residual feeding were recorded. On d 70, 12 broilers from each group were sampled for serum antioxidant and immune indexes measurement, intestinal morphological analysis, as well as 16S rRNA sequencing of cecal contents and short-chain fatty acid (SCFA) determination. Results In comparison to the NC group, the LD group had greater final body weight and average daily gain, and a lower feed conversion ratio (p < 0.05, d 1 to 70). However, in MD group, no significant change of growth performance occurred (p > 0.05). Furthermore, DOL supplementation significantly improved the levels of serum total antioxidant capacity, glutathione peroxidase, superoxide dismutase, and catalase, but reduced the level of malondialdehyde (p < 0.05). Higher serum immunoglobulin A (IgA) content and lower cytokine interleukin-2 (IL-2) and IL-6 contents were observed in DOL-fed broilers than in control chickens (p <0.05). Compared to the NC group, duodenal villus height (VH) and villus height-to-crypt depth (VH:CD) ratio were considerably higher in three DOL supplementation groups (p < 0.05). Further, 16S rRNA sequencing analysis revealed that DOL increased the diversity and the relative abundance of cecal bacteria, particularly helpful microbes like Faecalibacterium, Lactobacillus, and Oscillospira, which improved the production of SCFA in cecal content. According to Spearman correlation analysis, the increased butyric acid and acetic acid concentrations were positively related to serum antioxidant enzyme activities (T-AOC and GSH-Px) and immunoglobulin M (IgM) level (p < 0.05). Conclusion Overall, the current study demonstrated that supplementing the dies with DOL in appropriate doses could enhance growth performance, antioxidant capacity, and immune response, as well as gut health by promoting intestinal integrity and modulating the cecal microbiota in broilers. Our research may serve as a preliminary foundation for the future development and application of DOL as feed additive in broiler chicken diets.